Augmentation of Technology Enhanced Learning in 21st Century Education System A Survey Report on Schools in New Delhi - Malik, Sangeeta; Sharma, Usha (JOURNAL OF INDIAN EDUCATION, 2016)
Learning is a process of expanding one’s knowledge in a desired sphere. “System” here is a premeditated mechanism which facilitates learning to be more efficient and meticulous. A system which is adequately potent to assist the escalation in learner’s knowledge would be considered as an eloquent learning system. In the 21st century, there has been a noticeable augmentation of “Technology Enhanced Learning” or learning through “Multimedia Learning System” which has modified the conventional learning methodologies and systems to a great extent. With an aim to study and evaluate the potential of the latest prevailing learning systems in the country, a survey has been carried out in six different schools of New Delhi, India, all belonging to diverse categories. A part of the analysis of this survey is presented in this paper.